Complex Evaluation Model of Corporate Energy Management - Ágnes Kádár Horváth (Theory, Methodology, Practice, 2014)
With the ever increasing energy problems at the doorstep alongside with political, economic, social and environmental challenges, conscious energy management has become of increasing importance in corporate resource management. Rising energy costs, stricter environmental and climate regulations as well as considerable changes in the energy market require companies to rationalise their energy consumption and cut energy costs. This study presents a complex evaluation model of corporate energy management, which can be used for identifying corporate challenges resulting from global energy crises and for seeking possible answers to them as well as enabling companies to evaluate their current energy management practices and identify the level of their energy consciousness. This model enables companies to rethink their energy management tasks and identify the most acute problems of their energy management practices.